Knowledge-based marketing : the twenty-first century competitive edge - Chaston, Ian (SAGE, 2004)
In recent years even governments around the world are beginning to understand that knowledge is a critical contributor to stimulating the rapid growth of entire economies. It is argued that in a modern economy, knowledge is the most important resource within the companies based within any country.